MR Imaging of Parotid Tumors: Typical Lesion Characteristics in MR Imaging Improve Discrimination between Benign and Malignant Disease - Christe, A. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: The surgical approach to parotid tumors is different for benign and malignant neoplasms, but the clinical symptoms do not correlate well with histology. Difficulties in tumor classification also arise in imaging modalities, in which sonography has the lowest and MR imaging, the highest accuracy. The purpose of this study was to review our experience using conventional MR imaging of the neck in the evaluation of parotid tumors and to evaluate which MR imaging findings are best able to predict malignant histology. MATERIALS AND METHODS: Eighty-four consecutive patients (43 males, 41 females; median age, 56 years; range, 9–85 years) with parotid gland tumors who underwent MR imaging before surgery were prospectively included in the present study and retrospectively analyzed. Histology was available for all tumors. We analyzed the following MR imaging parameters: signal intensity, contrast enhancement, lesion margins (well-defined versus ill-defined), lesion location (deep/superficial lobe), growth pattern (focal, multifocal, or diffuse), and extension into neighboring structures, perineural spread, and lymphadenopathy. RESULTS: The 57 (68%) benign and 27 (32%) malignant tumors consisted of 29 pleomorphic adenomas, 17 Warthin tumors, 11 various benign tumors, 5 mucoepidermoid carcinomas, 3 adenoid cystic carcinomas, 1 acinic cell carcinoma, 1 carcinoma ex pleomorphic adenoma, 9 metastases, and 8 various malignant neoplasms. Specific signs predictive of malignancy were the following: T2 hypointensity of the parotid tumor (P = .048), ill-defined margins (P = .001), diffuse growth (P = .012), infiltration of subcutaneous tissue (P = .0034), and lymphadenopathy (P = .012). CONCLUSIONS: Low signal intensity on T2-weighted images and postcontrast ill-defined margins of a parotid tumor are highly suggestive of malignancy.